The Role and Importance of the Joint Work of Preschool Educational Institutions and Parents on Environmental Education of Preschoolers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
what is a global environmental problem implemented through the environmental education program for preschoolers? The role of plants and animals in solving a global problem. The influence of nature on a child is huge! It is at preschool age that the assimilation of the basics of environmental knowledge is most productive, since the baby perceives nature very emotionally, as something alive... Abstract: there is a global environmental problem, implemented through the environmental education of preschool children? The role of plants and animals in the solution of global problems. The influence of nature on the child’s huge! In the preschool years mastering the fundamentals of ecological knowledge are most productive, as the baby perceives the very emotional nature, as something alive...